UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN MEKAI (Pycnarrhena cauliflora DIELS.) TERHADAP Staphylococcus aureus - Yayuk Bulam Sarifati; Sjarif Ismail; Khemasili Kosala (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Mekai leaves (Pycnarrhena cauliflora Diels.) (P. cauliflora). Are known to contain flavonoid compounds, tannins and phenolics that act as antibacterial agents and are used in the treatment of eye pain. Staphylococcus aureus (S. aureus) is one of the examples of bacterial diseases of eye pain and also a major cause of many infections in communities and health facilities with cases of resistance to various antimicrobial agents. The purpose of this study was to prove the antibacterial activity of mekai leaves ethanol extract against S. aureus bacteria. This research is an experimental research. The stages of this research began by extracting mekai leaves using maceration method with 96% ethanol solvent. Antibacterial activity was tested by the disc method (Kirby-Bauer) using ethanol extract concentrations of mekai leaves (EPC) 20%, 30%, 40%, 50%, 60%, 70%, and 80%, positive control using 25 μg amoxicillin and negative control using DMSO 10%. The measurement results of inhibition zones of mekai leaf ethanol extract 20%, 30%, 40%, 50%, 60%, 70% and 80% respectively were 8.32 mm, 8.32 mm, 8.32 mm, 8.67 mm, 9.00 mm, 8.67 mm, and 8.33 mm. While the positive control measurement of 25 μg amoxicillin against S. aureus is 28.67 mm and the measurement of 10% negative DMSO control does not produce inhibitory zones, so it can be concluded that the ethanol extract of mekai leaves has antibacterial activity, but the area of ​​inhibition zone produced is smaller than amoxicillin 25 µg. The results of statistical tests using Mann Whitney between negative controls with all EPC concentrations obtained significant differences with p values ​​<0.05, it can be concluded that there is antibacterial activity produced at all EPC concentrations.